Implementation of web product search engine - Fu, Zixiang. (2011)
Online shopping is gaining popularity in recent years due to the convenience of purchasing products through the Internet without the need to be physically present at the shop. One challenge that online shops (e-Commerce) are facing today is allowing its consumer to look for the product they are searching within a short period of time. This in term leads to the popularity of search engine, which aims to answer a query in the shortest possible time with the most relevant results.